2019
DOI: 10.1053/j.jvca.2018.08.201
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Coagulation Parameters in Arterial and Venous Blood in Cardiac Surgery Measured Using the Quantra System

Abstract: Objective: Perioperative coagulation testing often is performed with arterial samples even though device reference ranges typically are established in venous samples. Although limited studies exist comparing coagulation parameters across sampling sites, viscoelastic testing devices have demonstrated some differences. The objective of this study was to compare coagulation parameters determined using the Quantra System for venous and arterial samples. Design: Prospective, observational study. Setting: Tertiary c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 18 publications
(22 reference statements)
1
18
0
Order By: Relevance
“…We only tested blood taken from the arterial cannula, as recommended by Groves et al. . Compared with before bypass, a significant decline in platelet count and fibrinogen was observed after bypass (after protamine).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We only tested blood taken from the arterial cannula, as recommended by Groves et al. . Compared with before bypass, a significant decline in platelet count and fibrinogen was observed after bypass (after protamine).…”
Section: Discussionmentioning
confidence: 99%
“…We studied patients undergoing urgent surgery for unstable cardiac disease, who were nearly all taking antiplatelet medication; 68% of patients were transfused Viscoelastic testing devices can be used before, during and after bypass to assess the coagulation system, but not all parameters during the three time-points are equally valid at predicting bleeding and guiding the use of blood products [2,7,9]. We only tested blood taken from the arterial cannula, as recommended by Groves et al [18]. Compared with before bypass, a significant Our study was not designed to change transfusion management, but rather to test the utility and feasibility of the Quantra System before, during and after bypass.…”
Section: Discussionmentioning
confidence: 99%
“…Output parameters include a series of clot times and clot stiffness values that represent the functional role of the major components of coagulation, including fibrinogen and platelets. The QPlus Cartridge parameter Fibrinogen Contribution to clot stiffness (FCS) has been previously shown to correlate with laboratory-based fibrinogen assays, whereas the Platelet Contribution to clot stiffness (PCS) parameter has been shown to integrate information about platelet number and platelet function [18][19][20][21][22][23]. A detailed description of the Quantra analyzer and the QPlus Cartridge parameters is presented elsewhere [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The QPlus Cartridge parameter Fibrinogen Contribution to clot stiffness (FCS) has been previously shown to correlate with laboratory-based fibrinogen assays, whereas the Platelet Contribution to clot stiffness (PCS) parameter has been shown to integrate information about platelet number and platelet function [18][19][20][21][22][23]. A detailed description of the Quantra analyzer and the QPlus Cartridge parameters is presented elsewhere [18,19]. The performance of the Quantra QPlus System has been established in a series of clinical studies in cardiac and spine reconstruction surgery [18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…58 Additionally, observational studies are attempting to lay groundwork for Quantraʼs potential clinical use by first assessing PLT contribution to clot stiffness in patients undergoing cardiac surgery and with some studies comparing its values to those of other VET. 58,60,[67][68][69][70] Only small in vitro studies have assessed Sonoclotʼs ability to monitor PLT function and detect therapeutic GPIIb/IIIa inhibition. One such study had found PF to be comparable to turbidimetric PLT aggregometry in its ability to detect pharmacological GPIIb/IIIa inhibition by tirofiban.…”
Section: Clinical Evidence For the Use Of Vet In Evaluating Plt Funmentioning
confidence: 99%